(untitled) (Journal of Asian Development Studies, 2025)
This research aims to bridge this research gap by discussing the nature of Chanu in terms of NPD, thus advancing our general understanding of narcissism as applied to the characterization of literature. This research paper examines how Narcissistic Personality Disorder (NPD) was portrayed in novel Brick Lane by Monica Ali by studying the character of Chanu. Whereas the concept of narcissism is depicted in the literature as a stable and even heroic quality, the characterization of the victims of NPD has undergone under-exploration, especially in this novel. The aim of the study will be to determine the psychological factors which led to the narcissistic nature of Chanu. The research applies a qualitative approach to the research and deploys the close textual analysis technique as popularized by David Greenham that uses the theoretical perspectives of Kohut to explain narcissism to structure the research. According to the findings, the character of Chanu has apparent signs of NPD, which are based on overemphasized self-importance and a sense of strong necessity to be validated, which greatly define his interactions and self-image. This study has value in literary criticism because it provides a combination of psychology and literature, provides a more in-depth view of the representation of mental health in fiction, and highlights the significance of subtle literary interpretation in helping the society to learn more about personality disorders.